Development of clearance verification equipment for uranium-bearing waste. (March 2019) - Yokoyama, Kaoru; Ohashi, Yusuke
Abstract: Dismantled materials generated from nuclear facilities are reused or directed to repository sites. If scrap metals with complicated shapes can be cleared, the amounts of radioactive waste can be reduced. A clearance verification system is constructed to determine the amount of uranium in decontaminated metals in a drum using the 1.001 MeV gamma rays of 234m Pa, produced in the decay of 238 U. The experimental study with simulated waste drums demonstrated that the quantification errors of uranium fall within 25% for 0.5 g of uranium. Highlights: A model to reduce uncertainty of quantitative determination of uranium content in a drum is applied. The 1.001 MeV gamma rays emitted by 234m Pa (a short-lived member of the 238 U decay-series) and the associated scattered gamma rays were used in this model. Relative errors between the quantitative values of uranium amounts and the true values were almost within ± 25%, for as little as 0.5 g.